(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
In the contemporary urban landscape, the design of co-working space holds significant implication for mental health well-being. Biophilia has contributed to creating built environment within the sense of nature which it can affect the human mental health and physical. Malaysia one of the developed countries among the Southeast Asia has been records that more than half of Malaysian employees admitted experience of the mental health disorder in co-working living space. The physical attributes provide psychological respite to the residents, alleviating tension and mental exhaustion by natural resources. To achieve this, some of systematic method alongside the narrative approach has been made, some of the studies has been found that the biophilia approach in space can help to reduce the human mental disorder such as stress, depression and anxiety. This research aims to examine which part of the element of biophilia are effective to reduce the human mental health and how the biophilia can connect between human feeling and emotion. As the result, this research has found out that these biophilia elements can give the positive impact to human mental health and enhancing the feeling and emotion. In contrast, the biophilia is the free resources that can heals our mental health by seeing the green environment and by appreciate the environment are enough to keep our mind relax and give our inner peace.